Wavelet based Enhancement Method for Satellite image Quality Improvement - C. Rajani, Ch. Pallavi, K. Khamarataj (International Journal of Advanced Science and Technology, 2020)
In image processing there are many enhancement methods have been proposed earlier to improve quality of satellite images. Despite of having advance steps still those methods unable to give satisfied result. There are many issues related to the satellite images it included edge enhancement also, as edges plays important role in information preservation. Therefore this new method is focus on edge preservation and enhancement. In this new method uses the concept of wavelet and morphological filtering. As the Gabor filter is used for efficiently detects the edges from image, while these detected edges are sharpened by using morphological filters. Also the other intermediate steps are applied so that it works on other important aspects such as noise removal, color and useful information preservation etc. This method gives better qualitative and quantitative result compare to the well known state-of- the-art techniques.